Bentall surgery for acute aortic dissection (type-a) in a patient with marfan syndrome (KYAMC Journal, 2018)
Background: Marfan syndrome is an autosomal-dominant hereditary connective tissue disorder with the clinical manifestations involving the ocular, skeletal, and cardiovascular systems. The cardiovascular manifestations include aortic root dilatation, aortic valvular insufficiency, mitral valve prolapse, mitral regurgitation, aortic dissection and aortic rupture. Acute aortic dissection is one of the most common catastrophes involving the aorta. A high index of suspicion is important in patients who have predisposing risk factors. Classification is based on the location of dissection and its duration. Stanford type A (De bakey type I /type II) dissection should be treated surgically in essentially all cases.Objective: To report our experience in Bentall surgery in Acute aortic dissection (type A ). The efficacy of right axillary artery cannulation was investigated.Materials & Methods: Patient with acute type A aortic dissection involving coronary sinuses with 3 vessels of the arch free of lesions underwent aortic valve with ascending aorta and hemiarch replacement with composite valve graft (Bentall procedure) and reimplantation of coronary arteries under moderate hypothermia. The axillary artery was used for arterial cannulation.Results: Weaning from CPB was smooth. Perioperative period was eventless. Follow-up Echo revealed normal cardiac parameters.Conclusion: Prompt establishment of the diagnosis, through focused physical examination and noninvasive imaging, followed by rapid medical and surgical therapy, are the only effective methods to alter survival in patients with acute aortic dissection.KYAMC Journal Vol. 9, No.-2, July 2018, Page 95-100